Theory on the legal action of non-existence of the administrative act that was born to legal life by error of the Administration causing serious damage (2016)
In Colombia there should be an action of non-existence of administrative acts, which eliminates the effectiveness of administrative acts that born into legal life by error of the Administration and violate fundamental rights, in order to prevent the imminent harm that may be caused. Moreover it would have the possibility of the guardianship action against official decisions, misnamed de facto proceedings, that could limit the effectiveness of administrative acts that born into legal life by error of the Administration.